Confrontation And Tolerance Of Cultures: Pro Et Contra; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 35 : Research Paradigms Transformation in Social Sciences (RPTSS 2017) - Kokarevich M. N. (2018, 2018)
Title screen